2007
DOI: 10.3748/wjg.v13.i9.1466
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic abscess induced by foreign body: Case report and literature review

Abstract: Hepatic abscess due to perforation of the gastrointestinal tract caused by ingested foreign bodies is uncommon. Pre-operative diagnosis is difficult as patients are often unaware of the foreign body ingestion and symptoms and imagiology are usually non-specific. The authors report a case of 62-year-old woman who was admitted with fever and abdominal pain. Further investigation revealed hepatic abscess, without resolution despite antibiotic therapy. A liver abscess resulting from perforation and intra-hepatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
165
1
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(184 citation statements)
references
References 28 publications
0
165
1
13
Order By: Relevance
“…Cellulose or other previously unidentified material may be found in patients undergoing endoscopy for choledocholithiasis or with a previous surgical intervention [2][3][4]. Hepatic abscess due to bezoar translation, through a fistula formation, based on chronic cholecystitis, is a possible chain of events, but to our knowledge has not been prior reported.…”
Section: S162mentioning
confidence: 87%
“…Cellulose or other previously unidentified material may be found in patients undergoing endoscopy for choledocholithiasis or with a previous surgical intervention [2][3][4]. Hepatic abscess due to bezoar translation, through a fistula formation, based on chronic cholecystitis, is a possible chain of events, but to our knowledge has not been prior reported.…”
Section: S162mentioning
confidence: 87%
“…Asimismo, describió que este motivo de consulta es la segunda indicación más frecuente de realización de EVDA de urgencias en niños después de la hemorragia digestiva y que la etapa preescolar (menores de 5 años) es el grupo etario con mayor incidencia (7). Cualquier CE es posible, siendo más frecuentes las monedas, el bolo alimenticio impactado y huesos de pollo o espinas de pescado (8,9). La ingesta de un palillo de dientes es rara, constituye en general el 9% de los casos (6); pero por su carácter cortopunzante y su tamaño se han documentado diferentes tipos de complicaciones secundarias a su perforación en el tracto gastrointestinal (TGI), incluyendo desde el alojamiento en pleura, hígado, pericardio, peritoneo, riñón, uréter y vejiga (10-15) hasta complicaciones más graves, como fistulas del duodeno con la aorta o la vena cava inferior (16)(17)(18).…”
Section: Discussionunclassified
“…Traditionally, the diagnosis of ingestion and localization unusual presentations of migrating foreign bodies and to plan management. CT is excellent in detection of foreign bodies because of its high resolution and accuracy (3). CT findings in this patient demonstrated that the needle passed directly from the duodenum into the liver.…”
mentioning
confidence: 82%
“…If the object is not recovered in stool, a radiograph is taken weekly to determine whether it has left the stomach and is progressing satisfactorily (5). Endoscopy may be helpful when performed early, i.e., before foreign body migration and mucosal healing (3). Ultrasonography and CT may help to diagnose these clude plain radiography, ultrasound, CT, upper gastrointestinal series, upper endoscopy, colonoscopy, laparotomy, and autopsy (2).…”
mentioning
confidence: 99%